Studies on Molecular Complexes of Naphthylamines - Srivastava, K.P.; Kant Shrivastava, Rishi (Asian Journal of Chemistry, 2010)
The stability constants and thermodynamic parameters of the electrondonor- acceptor complexes of p-benzoquinone, 2,6-dichlorobenzoquinone and chloranil with α- and β-naphthylamines have been calculated from the positions of the charge transfer bands using electronic absorption spectroscopy in carbon tetrachloride medium under high donor concentration. All the molecular complexes exhibit one chargetransfer band each in the wavelength region where neither donors nor acceptors have any absorption. All the molecular complexes are inferred to be of n-π type with 1:1 stoichiometry.